109k views
2 votes
(−t 4 −5t 3 −10t 2 )+(9t 3 +3t 2 −1)

1 Answer

3 votes

Answer:


\left(-t^4-5t^3-10t^2\right)+\left(9t^3+3t^2-1\right)=-t^4+4t^3-7t^2-1

Explanation:

Given the expression


\left(-t^4\:-5t^3\:-10t^2\:\right)+\left(9t^3\:+3t^2\:-1\right)

Remove parentheses: (a)=a


=-t^4-5t^3-10t^2+9t^3+3t^2-1

Group like terms


=-t^4-5t^3+9t^3-10t^2+3t^2-1

Add similar elements


=-t^4-5t^3+9t^3-7t^2-1
-10t^2+3t^2=-7t^2

Add similar elements


=-t^4+4t^3-7t^2-1
-5t^3+9t^3=4t^3

Thus, the equivalent expression in simplified form:


\left(-t^4-5t^3-10t^2\right)+\left(9t^3+3t^2-1\right)=-t^4+4t^3-7t^2-1

User XOneca
by
5.7k points